Finance and policy in the realization of the church values seized in 1922 - Ivanov Sergei, deacon (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Financial and politics aspects of the realization of the church values seized in 1922 under the pretext of rendering assistance to the starving people are analyzed in the article. Author examines relationship between People’s Commissariat for Finance and three organizations of the all-Russian C.E.C. in which possession were the seized values. The conducted study gives grounds to assert that no sales of the church values abroad for purchase of bread for starving people were carried out and the ﬁght against famine and it’s consequences was waged with the funds of the state Treasury. The seizure of the values from the churches in 1922 lasted too long time. The concentration of the values in Moscow took several years. Having “realized” values authorities initially announced preliminary and demonstrative purchase of the food at a very small amount — 1 million of gold rubles. Then the sale of the church values for soviet depreciated rubles made by the Central Committee for Famine Relief of the all-Russian С.E.C. to Narcomﬁ n according to agreement of 29 July 1922 was likewise presented by the soviet leaders. The article describes the history of the fruitless eﬀorts undertaken by the members of Pomgol CC to obtain the gold credits, and points out more correct oﬃcial cost of the seized values. As an important conclusion the author asserts that the policy of double standards pursued by the Narkomﬁn in the assessment of the seized church property let the ﬁnancial department under the pretext of ‘’famine relief’’ get a signiﬁ cant proﬁ t.